1996
DOI: 10.1111/j.1472-765x.1996.tb01113.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substrate on the radiation resistance of yeasts isolated from sausage meat

Abstract: The radiation resistance of a selection of yeasts isolated from sausages was assessed in phosphate-buffered saline and in sausage meat. The yeasts Candida zeylanoides, Debaryomyces hansenii and Trichosporon cutaneum exhibited sigmoidal survival curves in both substrates whilst the more sensitive Sporobolomyces roseus exhibited an exponential survival curve in buffer but a sigmoidal curve in meat. Irradiating C. zeylanoides, D. hansenii and T. cutaneum in sausage meat changed the shape of their survival curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These results can be explained by the protective effect of protein, fat, and carbohydrate in the RIMF. The composition of suspending menstruum in which the microorganism was exposed to ionizing radiation greatly affects the sensitivity of the microorganism to ionization radiation (McCarthy and Damoglou 1996; Jay 2000; Mayer‐Miebach 2005; Farkas 2006). McCarthy and Damoglou (1996) reported that the D 10 ‐value is dependent on suspending menstruum and increases with complexity (for example, protein, fat, or carbohydrate) of the food system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be explained by the protective effect of protein, fat, and carbohydrate in the RIMF. The composition of suspending menstruum in which the microorganism was exposed to ionizing radiation greatly affects the sensitivity of the microorganism to ionization radiation (McCarthy and Damoglou 1996; Jay 2000; Mayer‐Miebach 2005; Farkas 2006). McCarthy and Damoglou (1996) reported that the D 10 ‐value is dependent on suspending menstruum and increases with complexity (for example, protein, fat, or carbohydrate) of the food system.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of suspending menstruum in which the microorganism was exposed to ionizing radiation greatly affects the sensitivity of the microorganism to ionization radiation (McCarthy and Damoglou 1996; Jay 2000; Mayer‐Miebach 2005; Farkas 2006). McCarthy and Damoglou (1996) reported that the D 10 ‐value is dependent on suspending menstruum and increases with complexity (for example, protein, fat, or carbohydrate) of the food system. Patterson (1989) and Urbain (1986) explained the protective effect of food components to the competition between food components and microorganisms in food system for interaction with oxidative radicals formed during irradiation, thus reducing the effect of the radiation damage and making the organisms more resistant to ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Direct irradiation should be more effective than indirect irradiation; however, milk and infant formula are complex systems with protein, fat, and carbohydrate. It has been reported that compositional complexity may reduce the radiation damage to microorganisms by interaction with generated oxidative radicals during irradiation (McCarthy & Damoglou, 1996). Moreover, water activity ( a w ) plays an important role in radiation damage, as a low a w may reduce the generation of free radicals, reducing the indirect irradiation damage to the nucleic acid of micro‐organisms.…”
Section: Fundamentals and Developments Of Nonthermal Milk Processingmentioning
confidence: 99%